Front Cover: Highly hydrophilic cationic gold nanorods stabilized by novel quaternary ammonium surfactant with negligible cytotoxicity (J. Biophotonics 12/2019). Issue 12 (9th December 2019) - Salajkova, Sarka; Sramek, Michal; Malinak, David; Havel, Filip; Musilek, Kamil; Benkova, Marketa; Soukup, Ondrej; Vasicova, Pavla; Prchal, Lukas; Dolezal, Rafael; Hodny, Zdenek; Bartek, Jiri; et al.
Abstract : Cationic gold nanorods stabilized by quaternary ammonium salts (QAS) are a promising tool for photothermal destruction of cancer cells. However, cytotoxicity of the alkanethiol‐QAS limits their medical applications. A novel design of cationic surfactant composed of the quaternary ammonium group and ethylene glycol chain significantly reduces the compound cytotoxicity in the free state while allowing the preparation of stable nanorods with high cellular uptake and lysosomal localization. Further details can be found in the article by Sarka Salajkova, Michal Sramek, David Malinak, et al. (e201900024 ). Abstract : Cationic gold nanorods stabilized by quaternary ammonium salts (QAS) are a promising tool for photothermal destruction of cancer cells. However, cytotoxicity of the alkanethiol‐QAS limits their medical applications. A novel design of cationic surfactant composed of the quaternary ammonium group and ethylene glycol chain significantly reduces the compound cytotoxicity in the free state while allowing the preparation of stable nanorods with high cellular uptake and lysosomal localization. Further details can be found in the article by Sarka Salajkova, Michal Sramek, David Malinak, et al. (e201900024 ).